Examining The Impact of Profitability, Investment Decisions, And Dividend Policy on Firm Value: Evidence From Indonesian Listed Food And Beverage Companies - Dewa Ayu Ade Sintia Dewi; I Gusti Ngurah Bagus Gunadi; Gregorius Paulus Tahu (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2026)
A firm's optimal firm value can attract potential funding sources, such as investors. Firm value is defined as the performance of a company, which has the capacity to influence investors' perceptions regarding the allocation of investment funds in a company. The objective of this study is to examine the impact of dividend policy, debt policy, and profitability on firm value among food and beverage sector companies listed on the Indonesia Stock Exchange (IDX). The population of this study consists of food and beverage sector companies listed on the Indonesia Stock Exchange for the 2020–2023 period, with a total population of 93 companies. The sample size was determined using purposive sampling, resulting in 17 companies meeting the criteria for inclusion in this study, with a total of 85 observation data points. The data analysis techniques employed in this study encompass classical assumption tests, multiple linear regression analysis, coefficient of determination analysis, the Y-test, and the t-test. The findings of the study suggest a positive and significant relationship between profitability and firm value. Investment decisions do not exert a substantial influence on firm value. The dividend policy of a firm can exert a deleterious effect on the firm's value.